(untitled) (American Journal of Islam and Society, 2017)
Interactions between Latin Europeans and the Islamic world during the medieval period have received great attention in numerous scholarly studies. The focus of such works often consists of an attempt to delineate the construction of identities and the extent to which they were utilized to mark out an “other.” By contrast, one of König’s most important conclusions demonstrates that for medieval Arab-Islamic scholars writing about the Latin West, these Latin Christian societies “were often simply regarded as alternative manifestations of human life and its social and political organisation” (pp. 327-28). This is primarily a historiographical investigation with a macro-historical approach. König analyzes material spanning the early Islamic period (the seventh century) to the later medieval period (the fifteenth century) and covers a range of genres. It could be said that such an approach fails to critically analyze the motivations of individual Muslim authors, something that the author does acknowledge in his preface. However, such analyses lie beyond the scope of the project at hand. Furthermore, a macro-historical approach is necessary for challenging previous scholarship on the subject. Bernard Lewis asserted that the Latin West was perceived as a united barbaric monolith, one viewed at best with disinterest in the minds of Muslim writers – a view that continues to influence scholarship to this day ...